Evaluation of Homeostatic Model Assessment of Insulin Resistance amongst the Nonalcoholic Fatty Liver Disease Study Population (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: NAFLD has been recognized as a hepatic manifestation of Metabolic Syndrome (MetS) linked with Insulin Resistance (IR) and is currently considered as the hepatic component of the Metabolic Syndrome (MetS). NAFLD is strongly associated with IR and is mostly silent which is often discovered incidentally through elevated hepatic enzyme levels. The purpose of this study is to Evaluate IR amongst the Nonalcoholic Fatty Liver Disease (NAFLD) study population in CMCH.Materials and methods: A prospective hospital based cross sectional study was carried out in the Department of Biochemistry, Institute of Nuclear Medicine and Allied Sciences (INMAS) and Chittagong Medical College  Hospital (CMCH). One hundred and fifty (150) subjects aging between 18-60 years were included in this study by non-probability consecutive sampling method. IR was evaluated by HOMA-IR.  Results: It was found that insulin resistance was more among the cases than controls. Association between NAFLD and HOMA-IR status among the study population showed odds ratio 15.23 which was statistically significant, p = < 0.001.Conclusion: The findings of the current study suggest that there is insulin resistance in NAFLDJCMCTA 2023 ; 34 (1) : 111-115